Studi Komparasi Strategi Mind Map Dan Make A Match Terhadap Hasil Belajar Ipa Siswa Kelas V SD Muhammadiyah 2 Kauman Surakarta Tahun Ajaran 2015/2016 - Farida, Rindu Aulia Nurul; , Drs. Mulyadi SK, SH., M.Pd (2016)
This study aims to describe: (1) Differences in the use of learning outcomes IPA strategy and strategy Mind Map Make a Match on learning outcomes fifth grade science students of SD Muhammadiyah 2 Surakarta Kauman Doctrine year 2015/2016. (2) A better strategy between strategy and strategy Mind Map Make A Match to the learning outcomes fifth grade science students of SD Muhammadiyah 2 Surakarta Kauman Academic Year 2015/2016. This study included into the quantitative research. Data collection techniques using observation, testing, and documentation. Test instrument is used to test the validity and reliability testing. Data were analyzed using t-test technique which preceded the prerequisite test analysis, the test of normality and homogeneity test. Based on data analysis with a significance level of 5% obtained t> t table, namely 2.076> 2.002. And obtained a mean value between grade classes are taught using the strategy Mind Map and classes are taught using the strategy Make A Match 80.93> 74.40. The conclusion of this study were (1) there are significant differences between the strategies of the Mind Map and Strategy Make A Match to the learning outcomes IPA 2 class V SD Kauman Muhammadiyah Surakarta Academic Year 2015/2016. (2) strategy Mind Map is better than the strategy Make A Match in improving learning outcomes fifth grade science students of SD Muhammadiyah 2 Surakarta Kauman Academic Year 2015/2016.